Filling Gaps and Setting Boundaries: Examining Utilization of Health and Social services at JeffHOPE Student Run Clinics - Roy Wang; Amanda Guth; Alyssa Tate; Michele Ly; James Plumb (SAGE Publishing, 2021)
The objective of this study was to describe the frequency that healthcare and social support services offered by JeffHOPE, a student run clinic for people experiencing homelessness in Philadelphia, PA, were utilized by patients. This study also aimed to investigate where patients would seek medical care on a given day had they not been able to access JeffHOPE. This study was conducted via mixed methods consisting of retrospective chart review of patient encounter records and a patient survey conducted weekly throughout 2019, both at a single clinic site, and retrospective chart review of January through March 2020 records at 5 clinic sites. This study found that the frequency of services utilized varied between clinic sites, and that Pharmacy and Procedure committees were the most utilized when examining the combined clinic data. Additionally, the survey found that JeffHOPE provided medical care to those that otherwise would not have sought it. Clinics also served as an alternative to accessing care for non-emergent issues in an Emergency Department (ED) for some patients, but for others it replaced seeing their primary care provider (PCP). This study confirmed that the services offered by JeffHOPE are well-utilized by patients experiencing homelessness in Philadelphia. It also revealed that while the organization's medical services filled care gaps and potentially decreased unnecessary ED visits, they were also sometimes accessed in lieu of a PCP visit. A focused effort on linkage to formal primary care services for all JeffHOPE patients and expanding collection of more granular data to all clinics represent important future endeavors for this student run organization.